The Greatest Man In the World. The life and ethics of Albert Schweitzer in the eyes of students pursuing medical and legal degrees - Cybulski, Marcin; Strzelecki, Wojciech; Chmielowski, Paweł; Stelcer, Bogusław; Bilski, Bartosz; Grzymisławska-Cybulska, Maria (Journal of Medical Science, 2018)
Introduction. Albert Schweitzer (1875–1965) was an Alsatian doctor, philosopher-ethicist, theologist, lutheran pastor and musician-organ player and musicologist. In 1913 he started his medical practice in Lambaréné (Gabon) in which he built from scratch his greatest legacy – The Albert Schweitzer Hospital. Due to an involvement of doctors and nursing staff from all over the world this hospital has been functioning and developing to this day. In 1952 he was awarded the Nobel Peace Prize for his engagement into the promotion of peace, disarmament and the prevention of imperial arms race. Currently, his spiritual and scientific legacy constitutes an element of biophilic angle in academic curricula at all levels of education also in medical sciences mainly in the United States and Western Europe.Material and Methods. The research is based on a questionnaire evaluating the level of awareness of Albert Schweitzer’s person, his legacy and concepts. The survey was completed by 53 law students of the SWPS University of Social Sciences and Humanities in Poznan and 435 medical studies students of the University of Medical Sciences in Poznań. The respondents did the following various studies: medicine, dentistry, pharmacy, obstetrics, paramedicine, dietetics, optometry, physiotherapy and occupational therapy.Results. Only 5.5% (n27) of the students from both Universities know about Albert Schweitzer and his works. Albert Schweitzer is not perceived as a medical doctor, entrepreneur-philanthropist, lutheran pastor, political activist, musician, musicologist and the winner of the Nobel Peace Prize. Not many people have heard about the Reverence for Life (19%, n93), however, they recognise Albert Schweitzer’s connection to philosophy and ethics.Conclusions. Despite the Albert Schweitzer’s presence in the Polish bioethical debate and his popularity in the 60s to the 80s, today he becomes obsolete. Even at the university level education in the areas of science in which morality and ethics provide basic professional principles – an unaided recall of his name and works among young people is rare.